Herbal Teas for Managing Sleep Paralysis and Other Sleep Disorders: A Comprehensive Review - Hina Sharif; Tahmina Maqbool; Muznah Khan; Fareha Shahid; Syeda Rayya Maryam; Laiba Tahir (RADS Journal of Biological Research & Applied Science)
Background: Awareness of sleep paralysis holds a paramount position in our society. As studies suggest, herbal teas are widely accepted for the relief of stress, anxiety, and other symptoms of sleep paralysis and disorders.